Morphological characterization, pathogenicity screening, and molecular identification of Fusarium spp. isolates causing post-flowering stalk rot in maize - Harish, J.; Jambhulkar, Prashant P.; Bajpai, Ruchira; Arya, Meenakshi; Babele, Piyoosh K.; Chaturvedi, Sushil K.; Kumar, Anil; Lakshman, Dilip K. (Frontiers in Microbiology, 2023)
Post Flowering Stalk Rot (PFSR) of maize caused by the Fusarium species complex is a serious threat to maize production worldwide. The identification of Fusarium species causing PFSR based on morphology traditionally relies on a small set of taxonomic characteristics with only minor morphological variations among distinct Fusarium species. Seventy-one isolates were collected from 40 sites in five agro-climatic zones of India to assess the diversity of Fusarium spp. associated with maize crops showing symptoms of PFSR in the field. Based on morphological traits such as mycelial growth patterns and mycelial pigmentation, Fusarium isolates were divided into 9 clusters. In-vitro, Kharif, and Rabi seasons were utilized to investigate the pathogenicity of Fusarium spp.-causing PFSR. The isolates were judged to be virulent based on their ability to decrease seedling vigour in in-vitro situations and high disease severity in field experiments. Based on the examination of pathogenicity in in-vitro, Kharif, and Rabi field trials and molecular identification based on partial sequence of the translation elongation factor 1 α (Tef-1 α), the ten most virulent isolates, were F. acutatum (FUR11), F. verticillioides (Davanagere), Gibberella fujikuroi var. moniliformis (F59), F. acutatum (F10), F. verticillioides (Raichur), F. verticillioides (F21), F. andiyazi strain (F18), F. verticillioides (F13), F. verticillioides (FUR15), and F. verticillioides (FUG9). The distribution of virulent isolates is specific to a geographical location with a hot humid climate. Morphological characterization, molecular identification, and information on the geographical distribution of virulent Fusarium isolates will be helpful for the efficient management of PFSR, including screening for resistance in maize-inbred lines.